Workplace impression management through pleonastic English words/phrases in e-mail communication? Evidence from India. (20th June 2019) - Sethi, Deepa
The purpose of this paper is to examine how Indians manage impressions at the workplace through pleonastic English words/phrases in e-mail communication. A pilot study was conducted to identify the major courteous words frequently used in e-mails. It was carried out through focused interviews with 20 participants. Information obtained in qualitative research was summarised and subsequently used in creation of the questionnaire for the quantitative research purposes. The quantitative research included data collected from questionnaires distributed amongst 501 participants. This study establishes that usage of pleonastic English words/phrases in e-mail by the Indians is a crucial element of managing impressions. Demographics like: gender, type of organisation, age group also affect the usage of pleonastic English words/phrases. Pleonasm is an important rhetoric device, and e-mail is a vital part of written communication, yet few studies have examined the use of pleonasm in e-mails. While people might seem very task-oriented in their communication, this study shows that their everyday e-mail-writing practices play an important role in the process of leaving imprints on the receiver and also maintaining relationships by forming the right impressions.